2013
DOI: 10.1002/j.1532-2149.2013.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain‐releasing action of Platelet‐activating factor (PAF) antagonists in neuropathic pain animal models and the mechanisms of action

Abstract: The present results revealed the effectiveness in anti-allodynia of PAF antagonists in different nerve injury models, and the unique mode of action; long-lasting anti-allodynia effects mediated by spinal GlyRα3 with a competitive manner at the initial stage and the following non-competitive manner of inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The pain relieving effects of PAF receptor antagonists are long lasting. We have previously suggested that the anti-allodynia effect of PAF antagonists in sciatic nerve injured mice is at least in part mediated by spinal relief of PAF-induced dysfunction of GlyRα3 [8]. In agreement with this concept, the present results showed that the intrathecal introduction of siRNA of PAF receptor mRNA effectively improved bone cancer pain behaviors in FBC mice.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The pain relieving effects of PAF receptor antagonists are long lasting. We have previously suggested that the anti-allodynia effect of PAF antagonists in sciatic nerve injured mice is at least in part mediated by spinal relief of PAF-induced dysfunction of GlyRα3 [8]. In agreement with this concept, the present results showed that the intrathecal introduction of siRNA of PAF receptor mRNA effectively improved bone cancer pain behaviors in FBC mice.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, PAF signaling in the microenvironment of the spinal pain transduction system may be increased by bone cancer due to peripheral nerve injury. We have further revealed a unique mode of action of TCV-309; TCV-309 is a specific competitive inhibitor of PAF receptors [21], but the potency of TCV-309 intensified as a function of time after administration, and the mode of action changed from a competitive manner within several hours after the injection of TCV-309 to a non-competitive manner later [8]. The intensification of the anti-allodynia potency of TCV-309 and change in its mode of action to a non-competitive manner as a function of time led us to speculate about a different mechanism of action; such as down-regulation of PAF receptors by binding TCV-309 to PAF receptors in the later stage of after nerve injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The future use of PAFR‐KO mice (in addition to the use of pharmacological agents) will assist in understanding this loop. Moreover, given that intrathecal injection of a PAFR antagonist attenuates neuropathic pain (21) and PAF‐induced allodynia (34), the spinal cord is an important candidate area for functional study of the PAF–pain loop. Finally, LPCAT2 and PAFR were expressed in microglia of the spinal cord dorsal horn (7), but the roles of other cells in the production and action of PAF should be investigated in the context of the PAF–pain loop.…”
Section: Discussionmentioning
confidence: 99%
“…PSL was performed as previously reported (21). In brief, 8-wk-old male WT, LPCAT2-KO, or LPCAT1-KO (22) mice were anesthetized with isoflurane and partial ligation of the sciatic nerve was performed by tying off the distal one-third to one-half of the sciatic nerve connected to the spinal cord (at vertebrae L3-L5) according to the procedure described in rats by Seltzer et al (23) and adapted for mice by Malmberg and Basbaum (24).…”
Section: Psl Modelmentioning
confidence: 99%